Phenylmethylsulfonyl fluoride protects L-lysine transport in Schizosaccharomyces pombe against inactivation by ammonium ions - Horák, J; Sychrová, H; Kotyk, A (Biochimica et biophysica acta, 1990)
Ammonium ions inactivate the basic amino acid transport system in Schizosaccharomyces pombe in an irreversible manner. The inactivation is accompanied by a 4-fold decrease of KT of L-lysine transport, leaving its Jmax unchanged; phenylmethylsulfonyl fluoride protects the system against inactivation. In contrast, two basic amino acid transport systems in a gap1 mutant of Saccharomyces cerevisiae are influenced by NH4+ ions in such a way that only the Jmax decreases while the KT of L-lysine transport is unchanged. Phenylmethylsulfonyl fluoride does not act here as a protective agent.
Keywords: Biological Transport; časové faktory; Saccharomyces cerevisiae; lysin; Phenylmethylsulfonyl Fluoride; mutace; Lysine; Sulfones; biologický transport; Ammonia; Schizosaccharomyces; Mutation; Saccharomycetales; Time Factors; sulfony; amoniak; fenylmethylsulfonylfluorid